Public Finances of India: Are you surprised? - Vadra, Ratna (International Journal of Economics and Financial Issues, 2021)
Public finances in India are at a turning point. Analysis of the past data shows that no major improvement in any of the major fiscal indicators. Restructure of debt, reforms in power sector and implementation of other issues under MTFRP hold promise for future. The Centre is carefully treading the path of fiscal prudence but State finances are slipping. The main objective of this paper is to suggest restructuring of public finances of the Centre and state governments to provide macroeconomic stability, equitable growth in the country and improve efficiency of resources. The paper also suggests ways to augment revenue resources and contraction in expenditure On the contrary, other fiscal indicators have shown significant deterioration. Thus the claims about fiscal adjustment are illusory. Fiscal consolidation in India perhaps need more attention and commitment. A comparison of deficits of Centre and state are made from period 1991-92 to 2016-17. Keywords: Public Finance, India, revenue, expenditure, deficits. JEL Classifications: H1, H2, H5, H7 DOI: https://doi.org/10.32479/ijefi.11732